PERMAINAN TRADISIONAL DI PAUD : KONTRIBUSI UNTUK PENGEMBANGAN KETERAMPILAN DAN MORAL ABAD 21 - Jumiatmoko, Jumiatmoko; Nafiah, Sarah Sausan; Rohmah, Fina (Jurnal AUDI: Jurnal Ilmiah Kajian Ilmu Anak dan Media Informasi PAUD, 2025)
The traditional game is one of the cultures that has been passed down from generation to generation by every community in various regions and has its types and benefits. In the era of technological developments that are all sophisticated today, it has resulted in traditional games being eliminated and replaced by the use of online games which attract more attention to children's playing activities. The purpose of this study is to identify several implementations of traditional games in Java that can rebuild local wisdom values ​​in everyday life and integrate traditional games into learning and playing activities related to aspects of child development. The research method used is descriptive qualitative with the method of literature study or literature review. Through several sources and reading materials, explanations are related to three traditional Javanese games, namely engklek, gobag sodor, and dakon. The results of this study are traditional Javanese games are able to instill a love for the homeland for children and provide understanding to teachers with three traditional games that can be applied to children's learning and playing environments and stimulate aspects of child development from an early age.